The Effectiveness And Sustainable Effects Of Sensory Imagination Program In Enhancing Figural Creativity Of Gifted Elementary Students In Saudi Arabia - Alhejoj, Arwa Faisal Khader (2022)
The Sensory Imagination Program (SIP) is a newly developed program aimed at enhancing figural creativity of gifted elementary students in Saudi Arabia. The effectiveness of SIP and its sustainable effects in enhancing figural creativity in terms of originality, flexibility, fluency and elaboration were tested empirically. The quasi-experimental design was carried out to test the effectiveness of SIP. The subjects of this study comprised of experimental group (n=31) and control group (n=31). The instrument used to measure figural creativity was Torrance Tests of Creative Thinking-Figural (TTCT-Figural). The experimental group undergone a 15 sessions of SIP training. Data for the research were collected during pre-test, post-test and delayed post-test. The results of Analysis of Covariance (ANCOVA) showed that SIP was effective in enhancing figural creativity as there was significant differences in the post-test means between experimental and control groups after the pre-test scores were controlled [F (1, 59) = 24.60, p < 0.05]. Next, the results of Multivariate Analysis of Covariance (MANCOVA) proven that there was significant difference in post-test means of figural creativity in terms originality [F(1, 59) =5.06, p < 0.05], flexibility [F (1, 59 ) =10.70, p < 0.05], and fluency [F (1, 59) = 5.46, p < 0.05]. Differences between experimental and control group in elaboration was not significant [F (1, 59) =2.99, p > 0.05]. ANCOVA was carried out again, two months after the intervention ended.